Controlling Function of Corporate Governance to The Relevance of Accounting Earnings Information - Azis, Azolla Degita; Hurriyaturrohman; Sundarta, Muhammad Imam; Rizqi, Muhamad Nur (Jurnal Kajian Akuntansi, 2023)
The relevance of accounting earnings information is needed to help users of financial statements to make a decision. This research intends to expand previous empirical studies by examining more comprehensive corporate governance variables, which are the proportion of audit committees and commissioners, the role of financial accounting experts in the audit committee, and ownership structure to increase the relevance of accounting earnings information. The aim of this research is to examine whether controlling function held by the company in order to perform good corporate governance can affect to the informativeness of accounting earnings in Indonesia. This research method uses Pooled Least Square (PLS) with total sample 327 firm-year observations of Indonesian public companies from 2017 to 2019. The result shows that the existence of effective controling function by multiple large shareholder, accounting expert, audit committee, and board size can increase the relevance of earnings information that rely on financial statement. This research findings could be as an additional literature in financial accounting and corporate governance area, and also for practitioners in manufacturing company in Indonesia that if a firm has good controlling function, it can provide relevant information about earnings to shareholders.